A Discussion on ICD-10 Coding of Infantile Diarrheal Disease. (August 2014) - Zhu, Daqiao; Yong, Lijiang; Zhang, Wenjun; Huang, Shaoyong
Abstract Purpose. To increase the accuracy of coding for infantile diarrhea. Method. Case records of diarrhea, from January 2011 to December 2013, were searched in a hospital through the medical record management system, and the coding on the front page of the records was subjected to retrospective investigation and analysis. Results. During these years, 5.44% of all discharged patients were cases of infantile diarrhea, the majority of which were infants, accounting for 61.27%, followed by children, accounting for 17.27%. In 2011 and 2012, the codes for infantile diarrhea were mistakenly classified as K52.9. Through reviews of medical records, it was found that as a matter of fact, infectious diarrhea accounted for 70.49%, and non-infectious diarrhea accounted for 29.56%. Conclusion. The hospital should reinforce the training given to clinicians in writing the front page of medical records, along with ICD-10 training. The staff involved in the coding work should communicate with clinicians better, thereby enabling a continuous increase in the accuracy of coding for infantile diarrhea.